The Safety and Impact of a Model of Intermittent, Time-Restricted Circadian Fasting (“Ramadan Fasting”) on Hidradenitis Suppurativa: Insights from a Multicenter, Observational, Cross-Over, Pilot, Exploratory Study - Damiani, Giovanni; Mahroum, Naim; Pigatto, Paolo Daniele Maria; Pacifico, Alessia; Malagoli, Piergiorgio; Tiodorovic, Danica; Conic, Rosalynn RZ; Amital, Howard; Bragazzi, Nicola Luigi; Watad, Abdulla; Adawi, Mohammad (Nutrients, 2019)
Hidradenitis suppurativa (HS) is a chronic-relapsing and debilitating disease, which affects the components of the folliculopilosebaceous unit and severely impacts on the perceived health-related quality of life. Among the possible treatments, dietary interventions, such as fasting, have been described to positively impact on HS. However, nothing is known about the effects of circadian, intermittent fasting, such as the Ramadan fasting. A sample of 55 HS patients (24 males (43.6%) and 31 females (56.4%), mean age 39.65 ± 8.39 years, average disease duration 14.31 ± 7.03 years) was recruited in the present study. The “Severity of International Hidradenitis Suppurativa Severity Score System” (IHS4) decreased significantly from 11.00 ± 5.88 (before Ramadan) to 10.15 ± 6.45 (after Ramadan), with a mean difference of −0.85 ± 0.83 (p < 0.0001). At the univariate analyses, the improvement was associated with HS phenotype (with a prominent improvement among those with ectopic type), treatment (with the improvement being higher in patients receiving topical and systemic antibiotics compared to those treated with biologics), the “Autoinflammatory Disease Damage Index” (ADDI), and Hurley scores. At the multivariate regression analysis, only the Hurley score (regression coefficient = 0.70, p = 0.0003) was found to be an independent predictor of change in the IHS4 score after fasting. The improvement in the IHS4 score was not, however, associated with weight loss. In conclusion, the Ramadan fasting proved to be safe and effective in HS patients. Considering the small sample size and the exploratory nature of the present investigation, further studies in the field are warranted, especially longitudinal, prospective and randomized ones.